Kehujjahan Hadis Mursal Perspektif Ibn Hazm (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
Mursal Hadith is narrated by old or small tabi’in to Prophet Muhammad Peace Be Upon Him (PBUH) whether it is come from words, deeds or his decisions. Based on the definition, the status of mursal hadith as determined by hadith scholars is judge to be hadis dhaif because the sanad of hadith is not connected to Prophet Muhammad (inqitha’) and the identity of narrator in the hadith is unknown (majhul). This research will try to answer the aunthenticity of the mursal hadits by mustasyaddid hadith scholar from Andalusia, namely Ibn Hazm. By using Library Research as the research method, it can be concluded that the criteria have been set by Ibn Hazm to determine the hujjah of mursal hadith does not accept hadith which is came from Ahl Madinah as hujjah. These criteria have implications especially for Ahl Madinah, Ibn Hazm automatically did not accept their hadis as hujjah even though his criticism was different from the other hadith scholar.
Keywords: Mursal Hadith; Hujjah; Ibn Hazm